Respuesta :

The root of an equation f(x) is the x value(s) for which f(x) = 0.

So, if you have f(x) = 6x + 3, to find its root(s), you do 0 = 6x + 3, and then

0 - 3 = 6x + 3 - 3

-3 = 6x + 0

-3 = 6x

-3/6 = 6x/6

-1/2 = x

x = -1/2 is the one and only root (Linear functions will always have 0 or 1 root. They will have zero roots if they are horizontal lines of the form y = c, where c is any constant, and they will have one root if they are of the form y = mx + b, where m is not 0.)

Hello there!

Answer: ⇒⇒ [tex]x=-\frac{1}{2}[/tex]

________________________________________________________________

Step-by-step explanation:

First you had to subtract by 3 from both sides of equation.

[tex]6x+3-3=0-3[/tex]

Simplify.

[tex]6x=-3[/tex]

Then you divide by 6 from both sides of equation.

[tex]\frac{6x}{6}=\frac{-3}{6}[/tex]

Simplify.

[tex]\frac{6x}{6}=x[/tex]

[tex]\frac{-3}{6}=-\frac{1}{2}[/tex]

[tex]x=-\frac{1}{2}[/tex]

Answer⇒⇒⇒⇒ [tex]x=-\frac{1}{2}[/tex]

______________________________________________________________

Hope this helps!

Thank you for posting your question at here on brainly.

Have a great day!

-Charlie

__________________________________________________________________